Pengaruh Profesionalisme, Komitmen Organisasi, Locus Of Control dan Etika Profesi Pada Kinerja Auditor - Susila, I Made Artha Budi; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 23 No 3 (2018)DO - 10.24843/EJA.2018.v23.i03.p01, 2018)
A good audit quality can be generated if an auditor is able to pay attention to the factors that influence it. Professionalism, organizational commitment, locus of control (internal) and professional ethics are some factors that may affect audit performance. This study aims to obtain empirical evidence of professionalism, organizational commitment, locus of control (internal) and professional ethics on audit performance.The location of this research was conducted at seven Public Accounting Firm in Bali Province with total sample of 66 auditors. The sample was chosen using saturated sampling technique. Data collection in this research using survey method with questionnaire technique. Data analysis technique used is Multi linear regression technique.Based on the analysis conducted, professionalism, organizational commitment, locus of control (internal) and professional ethics have significant and positive effect on audit performance. This study conclude that if the auditors are be able to increase their profesionalism, organizational commitment, locus of control (internal) and professional ethics their audit performance will increase al well. Keywords: professionalism , organizational commitment , locus of control (internal)professional ethicsand audit performance